OBE Curriculum Design Integrated with SKKNI as a Pillar for Implementing Merdeka Belajar in the Mechanical Engineering Vocational Education Program - Ariwibowo, Bayu; Bahtiar, Fahmy Zuhda; Budiyanto, Budiyanto; Setiawan, Moh Arif (Universitas Negeri Semarang, 2024)
Graduates of the Vocational Education in Mechanical Engineering (PVTM) program at Ivet University have predominantly pursued careers in relevant fields of expertise. A total of 87% of alumni work as educators. According to the graduate profile, PVTM alumni are also projected to become industry instructors and entrepreneurs. However, a key issue arises regarding the implementation of the Indonesian National Qualification Framework (KKNI) curriculum in PVTM, which remains focused on less adaptable skills, leading to concerns about graduates' competencies in the industry. By integrating the concept of Outcome-Based Education (OBE) with the Indonesian National Work Competency Standards (SKKNI) in the technical schema, graduate competencies are expected to be strengthened and better recognized in the industry. This study aims to design an OBE-integrated curriculum aligned with SKKNI to support the implementation of the Merdeka Belajar Kampus Merdeka (MBKM) initiative in the Vocational Education in Mechanical Engineering program at Ivet University. The research employed the Borg and Gall research and development methodology, culminating in a hypothetical model represented by a draft curriculum ready for trial implementation. The findings resulted in an OBE-integrated curriculum draft aligned with SKKNI, targeting the Level IV Welding Inspector occupational schema, comprising: (1) Eighteen study topics forming eight core courses within the program; (2) A curriculum integrated with three key concepts: OBE, SKKNI, and Welding Inspector; (3) Study topics applicable to Merdeka Belajar activities such as independent studies, student exchange programs, and projects; (A survey of 10 expert respondents, where 83% strongly agreed, 12% agreed, and 5% were neutral regarding the draft curriculum's feasibility. Thus, it can be concluded that the developed curriculum draft is suitable for trial implementation.